Effects of Family Structure on Children's Use of Ambulatory Visits and Prescription Medications - Chen, Alex Y (Blackwell Science Inc, 2006)
OBJECTIVE: To examine the effects of family structure, including number of parents, number of other children, and number and type of other adults, on office visits, emergency room visits, and use of prescription medications by children. DATA SOURCE: The Household Component of the 1996–2001 Medical Expenditure Panel Survey (MEPS). STUDY DESIGN: The study consisted of a nationally representative sample of children 0–17 years of age living in single-mother or two-parent families. We used negative binomial regression to model office visits and emergency room visits and logistic regression to model the likelihood of prescription medication use. Our analyses adjusted for demographic and socioeconomic characteristics as well as measures of children's health and parental education and child-rearing experience. DATA COLLECTION/EXTRACTION METHOD: We combined 1996–2001 MEPS Full Year Consolidated Files and Medical Conditions Files. PRINCIPAL FINDINGS: Descriptive data showed that children in single-mother families had fewer office visits than children in two-parent families; however, the effect of number of parents in the family on children's office visits or use of prescription medications was completely explained by other explanatory variables. By contrast, children living in families with many other children had fewer total and physician office visits and a lower likelihood of using a prescription medication than children living in families with no other children even after adjusting for other explanatory variables. Children who lived with other adults in addition to their parents also had fewer office visits and a lower likelihood of using a prescription medication than children who lived only with their parents. CONCLUSIONS: Children living in families with many other children or with other adults use less ambulatory care and prescription medications than their peers. Additional research is needed to determine whether these differences in utilization affect children's health.